Faktor-Faktor yang Berhubungan dengan Pengetahuan Perawat Tentang Penyapihan Ventilasi Mekanik Di Ruang Perawatan Intensif Rumah Sakit Panti Rapih Yogyakarta - Irawati Hardjono, Ganes; Setya Widyastuti, Chatarina; Anjar Rina, Fransisca (I Care Jurnal Keperawatan STIKes Panti Rapih, 2021)
Background: Mechanical ventilation weaningis a collaborative action of multidisciplines. The nurse's knowledge plays an important role in assessing the readiness of the patient and observing it during the weaning process to support the success of the patient escaping from mechanical ventilation. Objective: The purpose of this study was to determine the factors related to the knowledge of nurses about mechanical ventilation weaning in the Intensive Care Room at Panti Rapih Hospital. Methods:This research is adescriptive analytic study with a cross sectional approach. The population of this study were all nurses who worked in the Intensive Care Room at Panti Rapih Hospital, Yogyakarta. The sample in this study was the total population, namely nurses in the Intensive Care Room, amounting to 48 respondents. The research instrument was avalid and reliable questionnaire on the level of knpwledge and influencing factors with a calculated r value of morethan 0.482 and cronbach alpha 0.75. Analysis using independent T-test and Spearman Results: The mean level of knowledge of respondents about mechanical ventilation weaning averaged 31.52 with CI7.458. Factors related to mechanical ventilation weaning knowledgein this studywereage (p-value:0.024), education (p-value:0.000), experience (p-value: 0.003), social and cultural (p-value: 0.009).), and sources of information (p-value:0.001). Meanwhile, the factors that were not related to knowledge of mechanical ventilation in this study were environment (p-value:0.115) and economy (p-value:0.231).